1999
DOI: 10.1002/j.2333-8504.1999.tb01815.x
|View full text |Cite
|
Sign up to set email alerts
|

ENGLISH PROFICIENCY AND DIFFERENCES AMONG RACIAL AND ETHNIC GROUPS IN MEAN SAT® AND GRE® SCORES: A LONGITUDINAL ANALYSIS

Abstract: Although limited proficiency in the language of a test is known to depress aptitude test scores, the changes that occur as proficiency rises over time have been less well studied. The objective here is to contrast longitudinal changes in test performance for persons who indicated that English was (EBL) or was not their best language (ENBL). Analyses were based on a sample of U.S. citizens and permanent residents (N=65,987 EBL and N=1,592 ENBL); each individual had taken both the Scholastic Assessment Test (SAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Two measures of educational achievement are SAT and Graduate Record Examination (GRE) scores, the two most commonly used standardized tests for college and graduate school admissions (Pennock-Roman, 1999). Table 23 presents a longitudinal analysis of raw scale scores of Latino groups on the GRE and the SAT over an approximately 6-year period.…”
Section: Educational Testing and Field Of Studymentioning
confidence: 99%
“…Two measures of educational achievement are SAT and Graduate Record Examination (GRE) scores, the two most commonly used standardized tests for college and graduate school admissions (Pennock-Roman, 1999). Table 23 presents a longitudinal analysis of raw scale scores of Latino groups on the GRE and the SAT over an approximately 6-year period.…”
Section: Educational Testing and Field Of Studymentioning
confidence: 99%
“…Nevertheless, its potential value for researchers and practitioners lies in providing an option for reducing subgroup differences in the testing of specified constructs of interest, such as ability, while retaining the advantages of paper-and-pencil tests. We also acknowledge that the magnitude of the multiple-choice subgroup difference was higher than that reported elsewhere for college admissions tests (i.e., standardized differences ranging from 1.24 to 1.42; Oswald, Schmitt, Kim, Ramsay, & Gillespie, 2004;Pennock-Roma ´n, 1999). As such, there may have been selection bias in the items we selected for the present study.…”
Section: Discussionmentioning
confidence: 76%
“…We acknowledge that the magnitude of the race-based subgroup differences from Study 1 was slightly higher than those reported elsewhere for college admissions tests (i.e., standardized differences ranging from 1.24 to 1.42; Oswald, Schmitt, Kim, Ramsay, & Gillespie, 2004;Pennock-Román, 1999). As such, there may have been selection bias in the items we chose for the present study.…”
Section: Limitations and Future Researchmentioning
confidence: 69%